A linguagem musical na educação infantil: contribuições da neurociência - Novais, Maria Vitória Bianconi Duarte (Universidade Federal de São Carlos, 2025)
This Final Course Work aims to identify contributions from Neuroscience that can support to the development of innovative didactic experiences that consider musical practices and learning as relevant to the integral development of children four and five yers old in Early Childhood Education. The articles written since 2013, in Portuguese, were selected from a systematic review with the Journal Portal of the Coordination for the Improvement of Higher Education Personnel (CAPES). The results indicate that musical language contributes to the development of the human psyche, in addition to stimulating experiences that promote cognitive, emotional, social and learning skills, especially when introduced in early childhood - a critical phase for brain plasticity. However, the review shows that, in general, neuroscientific studies do not take into account essential aspects of the neurobiological processes that involve musical language, such as, for example, the sociocultural, political and economic context that surrounds the subject. It also highlights the difficulty of integrating Neuroscience into current pedagogical practices, due to the resistance to adapting current curricula and established teaching methods, the lack of adequate resources and the need for specific and ongoing training for teachers.
Musical language in early childhood education: contributions from neuroscience
Keywords: Neurociência; Linguagem musical; Educação infantil; Neuroscience; Musical language; Preschool education; CIENCIAS HUMANAS::EDUCACAO